UPAYA MENINGKATKAN MOTIVASI BELAJAR MAHASISWA PSIK SEMESTER 2 DALAM PEMBELAJARAN DEMOKRASI DI INDONESIA MELALUI METODE PEMBELAJARAN ROLE PLAYING DI STIK BINA HUSADA PALEMBANG - Misnaini, Sari (IKIP Siliwangi Bandung, 2021)
This study aims to determine the implementation of Role-Playing learning methods in an effort to increase student learning motivation in the Standards of Competence Indonesia democracy in Indonesia ’PSIK Bina Husada Palembang. This research is Classroom Action Research (CAR) taken in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subject of the research is the Bina Husada PSIK students in the second semester of 2018 totaling 32 students. Data collection techniques using observation techniques, questionnaires, and interviews about the implementation of Role-Playing learning methods. Based on the results of the study concluded that the implementation of the Role Playing learning method has an effect on increasing the learning motivation of the second semester PSIK Bina Husada students as evidenced by an increase in the percentage of observation results of student learning motivation score of 11.25% from the first cycle of 70.97% increasing to 82, 22% in cycle II. In addition, based on the results of the questionnaire data analysis, it can be concluded that there is an increase in the score of student learning motivation by 9.04% from the score of the cycle I by 72.38% to cycle II by 81.42%. When viewed classically, student learning motivation categorized as moderate and high also increased from 72.38% to 81.42%. The results of interviews with lecturers and students regarding the implementation of the Role Playing learning method also received a positive response.